The "Bipartite" Structure of the First Genome of Ampelomyces quisqualis, a Common Hyperparasite and Biocontrol Agent of Powdery Mildews, May Point to Its Evolutionary Origin from Plant Pathogenic Fungi. (7th August 2021) - Huth, Lauren; Ash, Gavin J; Idnurm, Alexander; Kiss, Levente; Vaghefi, Niloofar
Abstract: Powdery mildews are among the most important plant pathogens worldwide, which are often attacked in the field by mycoparasitic fungi belonging to the genus Ampelomyces . The taxonomy of the genus Ampelomyces is unresolved, but well-supported molecular operational taxonomic units were repeatedly defined suggesting that the genus may include at least four to seven species. Some Ampelomyces strains were commercialized as biocontrol agents of crop pathogenic powdery mildews. However, the genomic mechanisms underlying their mycoparasitism are still poorly understood. To date, the draft genome of a single Ampelomyces strain, designated as HMLAC 05119, has been released. We report a high-quality, annotated hybrid draft genome assembly of A. quisqualis strain BRIP 72107, which, based on phylogenetic analyses, is not conspecific with HMLAC 05119. The constructed genome is 40.38 Mb in size, consisting of 24 scaffolds with an N50 of 2.99 Mb and 96.2% completeness. Our analyses revealed "bipartite" structure of Ampelomyces genomes, where GC-balanced genomic regions are interspersed by longer or shorter stretches of AT-rich regions. This is also a hallmark of many plant pathogenic fungi and provides further evidence for evolutionary affinity of Ampelomyces species to plant pathogenic fungi. The high-quality genome and annotation produced here provide an important resource for future genomic studies of mycoparasitisim to decipher molecular mechanisms underlying biocontrol processes and natural tritrophic interactions.